Respuesta :

For this case we must find the inverse of the following function:

[tex]f (x) = (x-6) ^ 2 + 7[/tex]

For this we follow the steps below:

Replace f (x) with y:

[tex]y = (x-6) ^ 2 + 7[/tex]

We exchange the variables:

[tex]x = (y-6) ^ 2 + 7[/tex]

We solve the equation for "y", that is, we clear "y":

[tex](y-6) ^ 2 + 7 = x[/tex]

We subtract 7 on both sides of the equation:

[tex](y-6) ^ 2 = x-7[/tex]

We apply square root on both sides of the equation to eliminate the exponent:

[tex]y-6 = \sqrt {x-7}[/tex]

We add 6 to both sides of the equation:

[tex]y = \pm \sqrt {x-7} +6[/tex]

We change y by [tex]f ^ {- 1} (x):[/tex]

[tex]f ^ {- 1} (x) = \pm \sqrt {x-7} +6[/tex]

Answer;

[tex]f ^ {- 1} (x) = \pm \sqrt {x-7} +6[/tex]

If it is a inverse function.